The Clinical Significance of High Antimicrobial Resistance in Community-Acquired Urinary Tract Infections - Maria G. Zavala-Cerna; Midrori Segura-Cobos; Ricardo Gonzalez; Isidro G. Zavala-Trujillo; Silvia F. Navarro-Perez; Jose A. Rueda-Cruz; Fernando A. Satoscoy-Tovar (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. Urinary tract infections (UTIs) affect up to 150 million individuals annually worldwide, mainly due to Escherichia coli (E. coli) and Klebsiella. The emergence and spread of multidrug-resistant (MDR) bacteria are increasing, representing one of the biggest threats for human health. The objective of our study was to describe antimicrobial patterns of resistance and identify risk factors associated with MDR uropathogens. Methods. We conducted a cross-sectional study in 296 patients with community-acquired UTI who underwent clinical and microbiologic analysis, and clinical associations to MDR uropathogens were investigated. Findings. Microbiological analysis included E. coli (55%), ESBL-E. coli (26%), Enterococcus (6%), Klebsiella (5%), and others (8%). Higher frequencies of MDR bacteria were found among ESBL-E. coli, with resistance to ampicillin (100%), ceftriaxone (96%), gentamicin (57%), ciprofloxacin (89%), and TMP/SMX (53%). However, they were sensitive to fosfomycin (6.6%), nitrofurantoin (1.3%), and carbapenems (0%). Fosfomycin MIC90 for ESBL-E. coli was 5.78 μg/mL. The only clinical variable with significant association to ESBL producers was the presence of comorbidities: hypertension and type 2 diabetes mellitus with an OR (95%CI) of 2.51.3−4.9p<0.01 and 2.81.2−6.7p<0.05, respectively. Conclusions. In the majority of cases, resistance rates to commonly prescribed antimicrobials in UTIs were high, except for fosfomycin, nitrofurantoin, and carbapenems. To provide appropriate treatment, both the identification of risk factors and the uropathogen would be important. An active surveillance in UTIs in the community is required since the proportion of ESBL producers is increasing.